A Case Report on Pyoderma gangrenosum - Gupta, Akshima; Vyshnavi, Kasu; Soumya, Myakala; Puranam, Yashaswini; Mounika, Pannala; Vanjari, Nikhil Kumar (Journal of Pharmacy Practice and Community Medicine, 2026)
Pyoderma gangrenosum is a rare dermatological condition characterised by ulceration of the skin. It is more frequently observed in adults than in children. It is associated with inflammatory bowel disease, rheumatoid arthritis and lymphoproliferative disorders. A 12-year-old female reported a lesion on the fore arm 1 year back and was on treatment. Now, she has complaints of lesions over arms and thighs covering almost 30% area associated with burning sensation and pain and was prescribed tablet prednisolone, tablet dapsone and tacrolimus ointment. Although Pyoderma gangrenosum is a rare disease, clinicians should suspect it in the presence of purplish wound edges with a necrotic centre. Surgical debridement, while necessary in other ulcers, can worsen the condition and is only applicable to self-detachable necrotic plaques.
Keywords: Chronic Inflammatory Dermatosis; Corticosteroid Therapy; Erythematous Lesions; Immunosuppressive therapy; Neutrophilic Dermatosis; Pathergy Phenomenon; Pyoderma; gangrenosum